Role of expression of the tumour-associated macrophage receptor, MERTK, in hepatocellular carcinoma. (23rd February 2017) - Mukherjee, Sujit; Pop, Oltin; Triantafyllou, Evangelos; Khamri, Wafa; Curbishley, Stuart; Thursz, Mark; Adams, David; Antoniades, Charalambos
Abstract: Background: Tumour-associated macrophages are implicated in progression of hepatocellular carcinoma by dampening immune responses. Experimental models show that activation of the tumour-associated macrophage receptor, tyrosine-protein kinase mer (MERTK), in myeloid cells promotes tumour progression by suppressing innate and adaptive responses. We sought to investigate the role of MERTK and its sister molecule, AXL, in patients with hepatocellular carcinoma. Methods: Immunohistochemistry and multispectral imaging were performed for MERTK, AXL, and various macrophage activation markers on explanted hepatocellular carcinoma tissue (n=10), regenerative nodules (5), dysplastic nodules (5), and cirrhotic liver (controls, 5). Immunophenotyping of circulating monocytes was done. In-vitro co-culture systems were developed to modulate tumour-associated macrophage MERTK expression and determine the effects on CD14+, CD4+, and CD8+ leucocyte function. Findings: Peripheral leucocytes in hepatocellular carcinoma had higher MERTK expression (22·4% vs 10·7%, p=0·01) and a higher ratio of MERTK to AXL expression (39·1:1 vs 4·6:1, p=0·03) than cirrhotic controls. Immunohistochemical analysis confirmed increased macrophage MERTK expression in hepatocellular carcinoma compared with cirrhotic and healthy controls (p=0·01 and p=0·02, respectively). In vitro, induction of MERTK expression in CD14+ antigen-presenting cells reduced CD8+ (2·9% vs 10·7%, p=0·02) and CD4+ (3·6% vs 1·0%, p=0·04) T-cell proliferative responses to class I and II restricted antigens, respectively, with concomitant reduction (1·18% vs 5·59%, p=0·03) in the early activation marker CD69 in CD8+ T cells at 24 h. Antibody-mediated blockade of MERTK restored mean fluorescence intensity of the early activation marker CD28 in the same cells (p=0·037). Interpretation: We have identified an expanded population of MERTK-expressing immunosuppressive tumour macrophages in hepatocellular carcinoma. These cells can suppress innate and adaptive immune responses. We have shown that AXL is not similarly upregulated. Inhibition of MERTK signalling restores macrophage activation, thereby potentially identifying a novel immunotherapeutic target in hepatocellular carcinoma. Funding: National Institute for Health Research academic clinical fellowship.